Sistem Informasi Penggajian Karyawan Pada Basnul Coffee Berbasis Web - Ikhwan, Ali; Fahrian, Arris (Lembaga Riset Ilmiah, 2022)
Technology is developing rapidly so that it encourages us to keep up with the times that use technology a lot. This is beneficial for individuals, companies or agencies and organizations in carrying out their duties. Basnul Coffee is one of the businesses that has advantages in the taste of food that leads to the taste of the Middle East and is combined with their delicious coffee. Managers have responsibility for employees in terms of monthly payroll, of course, by calculating the working days and working hours of employees. This needs to be updated in calculating the salaries of employees in order to aim to increase the effectiveness and accuracy of the data generated so that it can assist managers in completing their responsibilities to employees. From these suggestions, an employee payroll information system is needed, this system will play a role in calculating salaries, and filing monthly employee salary reports.